Pragnienie Realnego albo fantazmat Zewnętrza wśród nędzy językowo zdefiniowanego świata - Wojciech Kruszelnicki (Przestrzenie Teorii)
In my article I reconstruct the Lacanian notion of the Symbolical and explain why language constitutes its most important domain. Following Kojève, I argue that language introduces to the human world an insurmountable negativity – the “deadness of the word” which substitutes the continuity of a world experienced in its immediate intensity with a symbolical representation and conceptualization. The order of the symbolical, identified with cultural order, is further on confronted with the order of the real which after Lacan, and especially after Žižek, I understand as a metaphor of an inaccessible, non-phenomenological experience lived beyond consciousness and culture, that is in the phantasmatic Outside. I trace various figures and intuitions of thus conceived “Outside” in thinkers such as Maurice Blanchot, Emmanuel Levinas and Georges Bataille and I argue that at issue in their works might have been an intriguingly novel way of thinking about communication. In conclusion I tackle the question why the discussed path of contemporary French philosophy is worth elaboration, positing it all the while as a project of strictly utopian character.